Characterization of the physicochemical and phytochemical properties of Carrier Agent-Optimized Microencapsulated Sapinit (Rubus rosifolius Linn.) - Palomeno, Antonio M., Jr (College of Home Economic, University of the Philippines Diliman, 2023)
In this study, optimization and validation of different carrier agent combinations to predict desirable powder properties, characterization of the physicochemical properties of the carrier agent-optimized microencapsulated sapinit, and evaluation of the phytochemical properties of fresh sapinit and its processed forms were investigated. The optimization process was performed using combinations of gum arabic (GA), maltodextrin (MD), and soy protein isolate (SPI) as carrier agents. A carrier agent combination of 2.25% GA, 22.75% MD, and 0% SPI was selected as optimum. Validation experiments revealed that the selected combination accurately predicted a sapinit powder with excellent flow characteristic, more intense red color, and relatively high antioxidant properties. Characterization of the morphology showed that sapinit powder particles presented an irregular semi-spherical shape with wrinkled surfaces and a low average particle diameter of 5.40μm. The sapinit powder had average values of bulk density at 0.43g/mL, tapped density at 0.47g/mL, Hausner ratio at 1.09, and Carr’s compressibility index at 9.17%. Its moisture content (MC) was around the usual 2-4% MC for sugar-rich products and its water activity was < 0.3. The sapinit powder had average values of L* at 83.56, a* at 6.28, b* at 12.60, chroma at 14.08, and hue angle at 1.11. Processing temperature and the carrier agents used may have affected the physicochemical properties of sapinit powder. Freeze drying slightly (p-value < 0.05) increased while spray drying significantly (p-value < 0.05) decreased its total anthocyanin content and total phenolic content. This study indicated that sapinit can be microencapsulated using combination of gum arabic and maltodextrin with desirable physicochemical and phytochemical properties.